Debt Overhang versus Crowding Out Effects: Understanding the Impact of External Debts on Capital Formation in Theory - Abdullahi, Muhammad Mustapha; Abu Bakar, Nor Aznin Bt; Hassan, Sallahuddin B. (International Journal of Economics and Financial Issues, 2016)
This is a conceptual analysis of the relationships between external debt and capital formation geared towards a proper assessment and understanding the experiences of Sub Saharan African countries external debts experiences. The study established that debt in general and external debt in particular is a necessary evil that all economies survive with. During the five decades of external debt experiences in SSA, all indices have indicated adverse relationships amongst and between all variables of interest in these countries. Most important of the negative consequences was the debt overhang and crowding out effects and their attendant effects on the economies. The study has shown that it has negatively affected the positive development of capital formation being one of the essential macroeconomic variables for a sustained economic development. Keywords: External debts, Debt Overhang, Crowding out Effects, Capital formation. JEL Classifications: E60, H63, O55.